FACTORS AFFECTING THE INCIDENCE OF LOW BACK PAIN IN PORTER WORKERS: A SYSTEMATIC REVIEW - Indrawati, Indrawati; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT A musculoskeletal disorder caused by poor ergonomics is low back pain (LBP). Transportation workers generally use their bodies as a means of transportation, such as hauling, carrying, or transporting. Most construction industry workers still use human labor to move goods or materials. This review was processed through a systematic process that was certainly adapted to the Preferred Reporting Items for Systematic Review (PRISMA) stages. Google Scholar was used due to its ease of access as well as the large amount of literature that can be accessed for free. The articles were selected based on publications which were published in the time period from 2018 to 2022. Only 4 studies were selected from 273 publications that identified based on inclusion and eligibility criteria. The studies were conducted in Gwiyang market of Yogyakarta, Bandung, North Sumatra, and Malang Regency. In this systematic review, it is known from the four journals that the factors causing Low Back Pain complaints include work position, workload, physical intensity, and length of work. Workplace position, workload, physical intensity, and length of service all have a significant impact on the prevalence of low back pain. It is hoped that this systematic review will provide workers with advice to pay attention to their position while working, stretch their body muscles when they begin to feel tired, use the proper lifting position, adjust physical abilities, and apply a good and proper way of working so that there is no excessive workload that can interfere with workers' health. Key Word: Low Back Pain, Transport Workers, Review